2013
DOI: 10.1371/journal.pone.0059786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Montanide™ ISA 71 VG Adjuvant during Profilin Vaccination against Experimental Coccidiosis

Abstract: Chickens were immunized subcutaneously with an Eimeria recombinant profilin protein plus Montanide™ ISA 70 VG (ISA 70) or Montanide™ ISA 71 VG (ISA 71) water-in-oil adjuvants, or with profilin alone, and comparative RNA microarray hybridizations were performed to ascertain global transcriptome changes induced by profilin/ISA 70 vs. profilin alone and by profilin/ISA 71 vs. profilin alone. While immunization with profilin/ISA 70 vs. profilin alone altered the levels of more total transcripts compared with profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…Montanide™ ISA 71 VG has been used previously to immunize hens with Eimeria recombinant profilin protein because of the enhanced immune repertoire generated by this adjuvant (Jang et al, 2013). In the current study, this method of antigen administration proved to be the most superior for inducing antigenspecific serum IgY.…”
Section: Discussionmentioning
confidence: 74%
“…Montanide™ ISA 71 VG has been used previously to immunize hens with Eimeria recombinant profilin protein because of the enhanced immune repertoire generated by this adjuvant (Jang et al, 2013). In the current study, this method of antigen administration proved to be the most superior for inducing antigenspecific serum IgY.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, a peptide near the amino terminal end of S2 has been shown to induce a protective cell-mediated response [37]. The adjuvant used has been reported to stimulate both antibody and cell-mediated immune responses [38][39][40]. The addition of the HA2 domain of the influenza hemagglutinin has also been demonstrated to increase the immunogenicity and protective capacity of IBV S1, possibly by increasing thermostability [41].…”
Section: Discussionmentioning
confidence: 99%
“…As Jang et al . reported in their vaccination studies with poultry infected with different Eimeria strains, ISA 71 VG adjuvant combined with their antigen of interest provided superior humoral and cellular immune responses. Recent observations with IFN‐ γ ‐ and IL‐17‐deficient mice lead to the notion that the stimulation of a cellular response seems necessary to generate a protective vaccine against S. aureus .…”
Section: Discussionmentioning
confidence: 95%
“… have demonstrated that adjuvants direct isotype‐switching processes via inducing a certain cytokine pattern. FA and the Montanide ™ are known to increase the production of IFN‐ γ via Th1 stimulation, leading to a subclass switching towards IgG2a and should therefore be equally potent in inducing a protective immune response against gram‐positive bacteria .…”
Section: Discussionmentioning
confidence: 99%